Current Directions in Personality Psychology / Reading from the American Psychological Society (Pearson - Prentice Hall, 2005)
The American Psychological Society is dedicated to advancing psychology as a science-based discipline. Personality Defined: The Issues of Stability, Situation-Behavior Profiles as a Locus of Constistency, Moving Personality Beyond the Person-Situation Debate, The Role of Biological Mechanisms in Personality, Biological Bases of Maternal Attachments, The Role of Prenatal Maternal Stress in Child Development, The Psychobiology of Stress, Novelty Seeking and Reward: Implications for the Study, Personality in Action: Intrapersonal Processes, Emotional Regulation in Adulthood: Timing is Everything, Personality in Relational Contexts, Making Sense of Self-Esteem, Marital Conflict: Correlates and Structures and Context, Implications of Personality for Well-Being, Resilience in Development, Stress and Positive Emotion and Coping, Intelligence Predicts Health and Longevity but Why?, Critical Thinking Questions.